"Gay" or "Homosexual"? The Implications of Social Category Labels for the Structure of Mass Attitudes. Issue 2 (March 2018) - Smith, Brianna A.; Murib, Zein; Motta, Matthew; Callaghan, Timothy H.; Theys, Marissa
Multiple identity and identification terms are used in social science research on sexuality, including clinical terms such as "homosexual" and "heterosexual" and more colloquial terms such as "gay" and "straight." In this article, we show that far from being synonyms, these terms have consequences for attitudes about gay and lesbian rights. We begin by providing a historical overview of the terms "homosexual" and "gay and lesbian, " showing the different connotations that social groups have come to associate with these terms. We then analyze a split-ballot experiment embedded in the 2012 American National Election Study (ANES) and show that group identity and authoritarianism shape attitudes toward "homosexual" rights differently than "gay and lesbian" rights.